Hepatic arterial infusion chemotherapy (HAlC) versus sorafenib for hepatocellular carcinoma (HCC) in Barcelona Clinic Liver Cancer (BCLC) B/C: A systematic review and meta-analysis - Zhengqiang Chen; Yaotian Fan; Yuting Luo; Xiwen Ye; Zhen You (PLoS ONE, 2026)
Introduction and objectives Despite both hepatic arterial infusion chemotherapy (HAIC) and sorafenib being efficacious for hepatocellular carcinoma (HCC), choosing between them for Barcelona Clinic Liver Cancer (BCLC) stages B/C patients remains controversial. This meta-analysis aims to compare their therapeutic outcomes and prognoses in such patients. Methods Pubmed, EMBASE, and Web of Science databases were searched. The primary outcome of this meta-analysis is Overall Survival (OS), while secondary outcomes include Progression-Free Survival (PFS), tumor response rate, and the incidence of adverse events. The analysis has included a total of 18 studies, comprising 3008 patients in aggregate. Results The analysis revealed a combined Hazard Ratio (HR) for OS of 0.57 (95% CI 0.38–0.86) and for PFS of 0.46 (95% CI 0.38–0.57). Subgroup analysis by different HAIC regimens: FOLFOX-based HAIC regimens 0.28 (95% CI: 0.16–0.50), FP regimen 0.68 (95% CI: 0.25–1.87), New-FP regimen 0.60 (95% CI: 0.47–0.77), cisplatin-based HAIC 0.63 (95% CI: 0.47–0.85). The pooled ORs were: Complete Response (CR) 3.88 (95% CI 1.56–9.65), Partial Response (PR)4.72(95% CI 2.44–9.13), Stable Disease (SD) 0.83 (95% CI 0.45–1.53), Progressive Disease (PD) 0.35 (95% CI0.25–0.48, Objective Response Rate (ORR) 5.32 (95% CI 2.54–11.13), Disease Control Rate (DCR) 2.03 (95% CI 1.05–3.92). For adverse events (AEs), the overall incidence Odds Ratios (OR) was 0.53 (95% CI 0.06–4.82) and for grade 3−4 events, 0.49 (95% CI 0.28–0.85). Conclusions In Asian and African patients with BCLC stage B/C hepatocellular carcinoma, HAIC—particularly the FOLFOX regimen—confers superior overall survival and oncologic outcomes compared to sorafenib, with higher response and disease control rates and reduced disease progression.